THE EFFECT OF INTERNAL CONTROL AND THE VILLAGE FINANCIAL SYSTEM ON THE MANAGERIAL PERFORMANCE OF VILLAGE OFFICIALS (A Study in the Villages of West Limboto District) - Mochammad Arief Pratama; Harun Blongkod; Muliyani Mahmud (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to determine the influence of internal control and the village financial system on the managerial performance of village apparatus in the villages of West Limboto District. This research employed a quantitative method. The data used in this study were primary data collected through questionnaires distributed to village apparatus in West Limboto District, resulting in a sample of 118 respondents. The sampling technique used was purposive sampling. The analytical tool employed was multiple linear regression analysis. The results indicate that the Village Financial System has a positive effect on the Managerial Performance of Village Apparatus, whereas Internal Control does not have a positive effect on the Managerial Performance of Village Apparatus.